2023
DOI: 10.1038/s41541-023-00609-x
|View full text |Cite
|
Sign up to set email alerts
|

The Streptococcus pyogenes vaccine landscape

Abstract: Recent efforts have re-invigorated the Streptococcus pyogenes (Group A Streptococcus) vaccine development field, though scientific, regulatory and commercial barriers persist, and the vaccine pipeline remains sparse. There is an ongoing need to accelerate all aspects of development to address the large global burden of disease caused by the pathogen. Building on over 100 years of S. pyogenes vaccine development, there are currently eight candidates on a product development track, including four M protein-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 44 publications
0
44
0
4
Order By: Relevance
“…pyogenes isolates could provide rich information on vaccine coverage in our communities. The vaccine candidates undergoing clinical trials, such as the 30-valent vaccine, are the most promising tools to reduce GAS infection numbers [69–71]. On this note, under the assumption that all subtype emm alleles of a parent emm- type were covered by the 30-valent vaccine candidate [72], approximately 83 % of our invasive isolates and 61 % of our non-invasive isolates were covered or had documented evidence of cross-reactivity [70, 72].…”
Section: Discussionmentioning
confidence: 99%
“…pyogenes isolates could provide rich information on vaccine coverage in our communities. The vaccine candidates undergoing clinical trials, such as the 30-valent vaccine, are the most promising tools to reduce GAS infection numbers [69–71]. On this note, under the assumption that all subtype emm alleles of a parent emm- type were covered by the 30-valent vaccine candidate [72], approximately 83 % of our invasive isolates and 61 % of our non-invasive isolates were covered or had documented evidence of cross-reactivity [70, 72].…”
Section: Discussionmentioning
confidence: 99%
“…With the emerging recognition of the role of S. pyogenes pyoderma in the development of ARF and RHD, understanding whether low-burden detection of S. pyogenes in skin lesions may contribute to the immune priming implicated in RHD pathogenesis will be essential [8][9][10][34][35][36]. With restored global interest in the development of a vaccine against S. pyogenes and RHD [37], it is critical to have a robust understanding of the epidemiology and strain diversity of S. pyogenes infection. Molecular methods should be central in enhanced surveillance for S. pyogenes in high-burden settings to aid the design and assessment of future interventions against RHD.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA partially eased their restrictions in 2006 and have now lifted them entirely. 86 Introducing a vaccine that can protect against all GAS serotypes is challenging. Investigation of GAS whole genome demonstrated that GAS isolates have extensive genomic heterogenicity due to gene exchange and single nucleotide polymorphisms and subsequent protein sequence variations.…”
Section: Antimicrobial Susceptibilitymentioning
confidence: 99%